Changing times - Rhodes, Willard (International Library of African Music, 1959)
Ethnomusicologists and students of African music have too often become involved in the technicalities of music as an art, forgetting that it is one of the most spontaneous and revealing expressions of the inner life of the individual and the social group to which he belongs. Melville J. Herskovits, one of the first anthropologists to recognise the importance of music in culture, writes, “But it is at the core of anthropological thinking that each problem investigated be recognised as only one manifestation of one segment of man’s complex culture, and that it be studied with full consciousness of its wide implications.” In discussing the comparative study of music outside the Euro- American culture sphere he states, “For its implications lead us to some of the most fundamental truths about the nature and function of culture, and suggest the importance of the contributions that investigations carried on in this field can make to the study of culture as a whole.”
Keywords: Ethnomusicology; Church music; Music; Africa; Social Aspects; Black People; African Music